Feeding habits of the jaguar Panthera onca (Carnivora: Felidae) in Tortuguero National Park, Costa Rica - Arroyo-Arce, Stephanny (2018)
Although dietary studies are considered an important conservation tool, few studies have assessed jaguar (Panthera onca) diet in Costa Rica. Therefore, this study describes the diet composition of the jaguar in Tortuguero National Park, Costa Rica, carried out by analyzing and comparing carcass (n= 1 374), scat (n= 75) and camera trap (n= 3) data, collected between 2012 and 2016. Our results indicated that jaguar diet in this area consisted of at least 20 prey species. The green sea turtle (Chelonia mydas) was the most frequent item based on carcass data, while the white-lipped peccary (Tayassu pecari) was the major prey species according to the scat analysis. Our results highlight the importance of combining different methods to describe the jaguar feeding habits. Further research should focus on calculating jaguar and terrestrial prey species abundance in the study area, information that would help to complement our findings.